Kebijakan Pemerintah Dalam Pengembangan Usaha Dive Centre oleh Pengusaha Asing di Desa Pemuteran - Eva April Liliyana; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
This article reveals about business ownership dive by tourism entrepreneurs both foreign entrepreneurs (foreign citizens) as well as local entrepreneurs (Indonesian citizen) in Pemuteran village and its licensing business. Besides, it also discusses the form of policies set by the central government and local government related to foreign entrepreneurs who set up businesses dive tourism in order to protect assets belonging to the community, especially the local businessmen in the village of Pemuteran. Data were collecting using purposive sampling technique with qualitative descriptive in the form of a general overview of the Pemuteran village, establishment of tourism in the dive center by foreign businessmen and local businessmen in Pemuteran village and observations contained in the field notes and other explanations related to writing. These data are presented in the form of descriptions and documentation. Source of data obtained from the primary data and secondary data. Sources of primary data derived from observations to the test site and in-depth interviews. Secondary data sources such as reference books, journals and archives associated with the research. The data obtained are translated descriptively. The results showed, the number of foreign businessmen who make an effort dive center in the Pemuteran Village more when compared with local businessmen. Therefore, government policies are needed to make the rules - strict rules regarding foreign businessmen who opened the business in Pemuteran village Key Words : Policy, Dive Centre, Pemuteran Village